What makes mindful self-initiated expatriates bounce back, improvise and perform: Empirical evidence from the emerging markets - Singh, Sanjay Kumar; Vrontis, Demetris; Christofi, Michael (My University, 2022)
Drawing upon the self-determination theory (SDT), this study examines what makes individual employees leverage improvisational capability to act extemporaneously to find relevant solutions for enhanced task performance. Using supervisor-subordinate dyadic self-initiated expatriates (SIEs) samples, we used structural equation modeling (SEM) to examine this study's hypotheses. We found that mindfulness influences resilience and improvisation in the workplace. Furthermore, we found improvisation to mediate the influence of resilience on task performance. We discussed in detail the essential findings and their contributions to advance theory and practice in the field.
Keywords: Emerging markets; improvisation; mindfulness; resilience; self-initiated expatriates (SIEs); task performance